2020
DOI: 10.1016/j.hjdsi.2020.100493
|View full text |Cite
|
Sign up to set email alerts
|

Digital triage: Novel strategies for population health management in response to the COVID-19 pandemic

Abstract: The COVID-19 pandemic has created unprecedented challenges for the U.S. healthcare system due to the mismatch between healthcare system capacity and patient demand. The healthcare industry has been a slow adopter of digital innovation due to the conventional belief that humans need to be at the center of every healthcare delivery task. In the setting of the COVID-19 pandemic, however, artificial intelligence (AI) may be used to carry out specific tasks such as pre-hospital triage and allow clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 7 publications
0
72
0
1
Order By: Relevance
“…Less extreme situations in emergency physicians and trauma surgeons result in PTSD [ 73 , 74 ]. Numerous predictive models of COVID-19 prognosis in various individuals based on AI-driven algorithms have been designed and published [ 75 , 76 , 77 , 78 , 79 , 80 ]. Their ability to distinguish between favorable outcomes and demise is significantly accurate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less extreme situations in emergency physicians and trauma surgeons result in PTSD [ 73 , 74 ]. Numerous predictive models of COVID-19 prognosis in various individuals based on AI-driven algorithms have been designed and published [ 75 , 76 , 77 , 78 , 79 , 80 ]. Their ability to distinguish between favorable outcomes and demise is significantly accurate.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of the likelihood of patient’s survival during initial triage and hospitalization may augment the allocation of healthcare assets on the level of a ward, hospital, or larger geographical area. Triage and outcome prediction are very controversial areas of AI application with the medical community and public unprepared for these applications [ 77 , 93 ]. AI can improve resource allocation and help assess the countries’ preparedness by taking into account the dynamic of the spread and available resources, factors frequently minimized in classic epidemiological models [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nurse and the caller are able to have an informed discussion, and it allows the nurse to operate efficiently and quickly to come to a mutually agreeable plan. The chatbot was made available on the Mass General Brigham website so patients could access it before calling the hotline and decrease the call volume [99]. Healthcare workers' screening for COVID-19 symptoms and exposure before every shift is essential for the spread of infection control.…”
Section: Emergency Response and Covid-19mentioning
confidence: 99%
“…However, it has been shown that for some specific conditions, diagnosis via telemedicine could be as accurate as an in-person diagnosis when examination through telemedicine is feasible subject to limitations (Asiri et al, 2018). For example, AI can be used for digital triage to direct patients to the most appropriate medical center based on the resources and their condition before they show up in emergency rooms (Lai et al, 2020). As another example, it has been shown that blood draw and injections can be done with portable robots using AI more accurately and faster than a manual procedure (Zemmar et al, 2020).…”
Section: Tele-examination Of Patientsmentioning
confidence: 99%